PENGARUH GOOD CORPORATE GOVERNANCE DAN PENGENDALIAN INTERNAL TERHADAP PENCEGAHAN FRAUD - Pratomo Cahyo Kurniawan; Khairina Nur Izzaty (Sekolah Tinggi Ilmu Ekonomi Bank BPD Jateng, 2019)
This research was conducted to examine the effect of good corporate governance and internal control on fraud prevention. The study was conducted at BPR Gunung Rizki. A common problem in this study is that there are still cases of fraud that can threaten the company's going concern. The sampling technique used is total sampling using all members of the population. The technique of collecting data using a questionnaire distributed to all employees except the hygiene and security department. The analysis technique used is multiple linear regression analysis. The results of the analysis show that good corporate governance has a positive effect on fraud prevention. The results of the second analysis show that there is a positive influence between internal control and prevention of fraud.